Comparison of Oil Sorption Capacity of Nonwoven Sorbents. Issue 2 (March 2023) - Jiang, Peilin; Lou, Lihua; Ramkumar, Seshadri
Oil sorption capacity is one of the essential parameters to evaluate the practical performances of oil sorbent products. This study aims to compare the dynamic oil sorption capacity of industrial nonwoven sorbents, which were fabricated through the carding process, spun-bond technology, and composite processes. The oil sorbents were produced by polypropylene fibers or cotton fibers with different surface wettability. The study showed that raw cotton layers exhibited a higher oil sorption capacity than the other three samples: eight-layer thermal-bonded melt-blown polypropylene fiber nonwoven, polypropylene fibers on top and bottom with raw cotton layers in the middle, and polypropylene fiber melt-blown nonwovens. Comparatively, eight-layer thermal-bonded melt-blown polypropylene fiber nonwoven had the lowest oil sorption capacity. Moreover, the hydrophilic property can significantly enhance the water pick-up capacity of sorbents on both dynamic and static systems but reduce the maximum oil sorption ability. Overall, the major factors determining a nonwoven fabric's oil absorption performance are its fiber type, surface wettability, and hydrophobicity/hydrophilicity. Specifically, raw cotton, polypropylene fibers, or polypropylene fiber/cotton composite oil sorbents with low hydrophobicity and high hydrophobicity will contribute to high oil absorption ability. The advantage of raw cotton over polypropylene fibers is 3–7 times higher in oil absorption capability, environmentally friendliness, and sustainability, attributed to their hydrophobic ingredients, including pectin and waxes. From a structure angle, products with a loose structure and good mechanical properties ensure a balance between service life and oil absorption performance. Graphical abstract This research is to analyze the effect of fiber types, the structure of sorbents, and surface wettability on nonwoven oil sorption capabilities. We compared the oil sorption capacity of multiple nonwoven sorbents, which were fabricated through the carding process, spun-bond technology, and composite processes. The oil sorbents were produced by polypropylene fibers or cotton fibers with different surface wettability. Their dynamic and static hydrophilic properties and their associations with oil sorption capabilities were examined.